QOL-21. REAL-WORLD QUALITY-OF-LIFE AND HEALTH UTILITIES FOR PATIENTS WITH CNS CANCERS ON THE XCELSIOR PLATFORM. (14th November 2022) - Sabates, Alanis; Wood, Alayna; Lee, Hope; Swain, Andrew; Irizarry, Sabrina; Hinton, Chezney; Ginn, Sarah; Cole, Zac; Chavez, Gordon; Tadic, Kristina; Chuyka, Don; Federowicz, Bryan; et al.
Abstract: OBJECTIVE: xCures operates a direct-to-patient, real-world evidence platform according to the nationwide observational research protocol XCELSIOR (NCT03793088), which aggregates medical data in an FDA-compliant electronic database. There is a relative scarcity of published results on real-world Quality-of-Life (QoL) outcomes and resulting health state utilities for patients with Central Nervous System (CNS) cancers. We sought to use the xCures platform to help address this issue. METHODS: XCELSIOR participants were invited weekly to complete the EuroQol 5-Dimension (EQ-5D-5L) QoL survey. A EuroQol-endorsed model was used to estimate health state utilities from patient surveys. Survey results, utility estimates, and clinical information were analyzed to understand the influence of common mutations in glioma on patient reported outcomes. RESULTS: 30 patients (21 glioblastoma, 4 oligodendroglioma, 2 diffuse midline glioma, 2 diffuse astrocytoma, 1 Schwannoma) completed at least one EQ-5D-5L survey over the course of 9 weeks. Health state utilities were positively correlated (p< .03) with Karnofsky Performance Score (KPS). The average utility for EGFR-mutated patients (N=6) was .578 (SD=.334) while for EGFR-wildtype patients (N=7) it was .747 (SD=.227). The average utility for MGMT-methylated patients (N=13) was .816 (SD=.139) while for non-methylated patients (N=10) it was .583 (SD=.379). The average utility for IDH-mutated patients (N=9) was .789 (SD=.153) while for non-mutated patients (N=17) it was .685 (SD=.324). The average utility for patients with a 1p/19q co-deletion (N=4) was .837 (SD=.126) while for those without a co-deletion (N=8) it was .744 (SD=.244). CONCLUSION: The xCures platform has enabled the study of real-world QoL outcomes for patients with CNS cancers. This is the first report studying the influence of genetic mutations on QoL collected through patient reported outcomes. Future research aims to perform similar studies with larger number of patients.